2017
DOI: 10.4012/dmj.2016-306
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and biological effects of infiltration with biopolymers on 3D printed tricalciumphosphate scaffolds

Abstract: The aim of this study was to evaluate the influence of infiltrating 3D printed (TCP) scaffolds with different biodegradable polymers on their mechanical and biological properties. 3D printed TCP scaffolds with interconnecting channels measuring 450±50 µm were infiltrated with four different biodegradable copolymers. To determine the average compressive strength, a uniaxial testing system was used. Additionally, scaffolds were seeded with MC3T3 cells and cell viability was assessed by live/dead-assay. Uninfiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…The scaffold used in our study is a synthetic biodegradable composite or hybrid, based on the ceramic tri-calcium phosphate (TCP) that is infiltrated with the polymer poly(D,L-lactide-co-glycolide (PLGA), abbreviated as TCP-PLGA. The infiltration of polymers such as PLGA significantly improves the mechanical properties in comparison to non-infiltrated TCP scaffolds, therefore balancing the problem of brittleness [20][21][22] . PLGA was chosen among other polymers because in a previous work of our study group it demonstrated favourable mechanical and biological behaviour 20 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The scaffold used in our study is a synthetic biodegradable composite or hybrid, based on the ceramic tri-calcium phosphate (TCP) that is infiltrated with the polymer poly(D,L-lactide-co-glycolide (PLGA), abbreviated as TCP-PLGA. The infiltration of polymers such as PLGA significantly improves the mechanical properties in comparison to non-infiltrated TCP scaffolds, therefore balancing the problem of brittleness [20][21][22] . PLGA was chosen among other polymers because in a previous work of our study group it demonstrated favourable mechanical and biological behaviour 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of polymers such as PLGA significantly improves the mechanical properties in comparison to non-infiltrated TCP scaffolds, therefore balancing the problem of brittleness [20][21][22] . PLGA was chosen among other polymers because in a previous work of our study group it demonstrated favourable mechanical and biological behaviour 20 . The scaffolds were produced by 3D printing based on principles of CAD/CAM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations